2021
DOI: 10.1002/cpdd.936
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Dose‐Finding Phase 1b Study of Subcutaneous Atezolizumab in Patients With Locally Advanced or Metastatic Non–Small Cell Lung Cancer

Abstract: Intravenous (IV) atezolizumab is approved for non-small cell lung and other cancers. Subcutaneous (SC) atezolizumab coformulated with recombinant human hyaluronidase, a permeation enhancer for SC dispersion and absorption, is being developed to improve treatment options, reduce burden, and increase efficiency for patients and practitioners. IMscin001 (NCT03735121), a 2-part, open-label, global, multicenter, phase 1b/3 study, is evaluating the pharmacokinetics (PK), safety, and efficacy of SC atezolizumab. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
(201 reference statements)
0
9
0
Order By: Relevance
“…Fortunately, a wide range of k a values were simulated as part of this study and should cover k a values of most antibody therapeutics with rhuPH20. It is also worth noting that the respective population PK model parameters for atezolizumab , and pertuzumab used in this study were derived from clinical trials where each molecule was co-formulated or co-administered with rhuPH20. The second case involves molecules exhibiting significant target-mediated drug disposition, which means that target engagement leads to more rapid clearance, usually manifesting as non-linear PK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, a wide range of k a values were simulated as part of this study and should cover k a values of most antibody therapeutics with rhuPH20. It is also worth noting that the respective population PK model parameters for atezolizumab , and pertuzumab used in this study were derived from clinical trials where each molecule was co-formulated or co-administered with rhuPH20. The second case involves molecules exhibiting significant target-mediated drug disposition, which means that target engagement leads to more rapid clearance, usually manifesting as non-linear PK.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, subcutaneously administered IgG + 1CTK molecules either directly absorb into the central compartment or get processed by carboxypeptidase into IgG + 0CTK; a 6 h delay in the carboxypeptidase activity was also included to account for equilibration of the SC depot with the surrounding SC interstitial fluid (Figure S1). PK simulations were performed using the respective model-estimated clearance (CL), central compartment volume of distribution ( V c ), peripheral compartment volume of distribution ( V p ), intercompartmental clearance ( Q ), SC bioavailability ( F ), and absorption rate constant ( k a ) from either atezolizumab , or pertuzumab population PK models (Table ). Additional parameters of the model used for simulation included the absorption rate constant ( k a,CTK ) and bioavailability of the IgG + 1CTK molecule ( F CTK ), which were assumed to be the absorption rate constant and 50% of the bioavailability of the parental IgG + 0CTK molecule, respectively (the rationale for these two assumptions are discussed in the Results section).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…As some patients with cancer who received ICIs achieve long-term survival and are able to continue receiving them for extended periods of time, companies are also developing ICIs that can be administered subcutaneously in the pursuit of improving convenience during long-term administration and to gain approval for alternative routes of administration. Not only the subcutaneous formulations of approved ICIs, such as nivolumab (NCT03656718), pembrolizumab (NCT04956692), a t e z o l i z u m a b ( N C T 0 3 7 3 5 1 2 1 ) , a n d d u r v a l u m a b (NCT04870112), but also newer agents such as sasanlimab and envafolimab have completed phase I trials and are in further development without any notable safety differences compared with the intravenous formulations, and it will not take long before they are approved and become part of our treatment options (43,45,64).…”
Section: Subcutaneous Pd-1/pd-l1 Inhibitorsmentioning
confidence: 99%
“…45 Atezolizumab, PD-L1 inhibitor, is also being investigated for SC administration and phase I studies have been successfully concluded. 46 Finally, a couple of new mAbs have also been developed in the SC form. Phase I study of sasanlimab demonstrated its antitumour activity across various tumour types and routes of administration.…”
Section: Sc Administration Of Mabs In Oncologymentioning
confidence: 99%